2016
DOI: 10.1177/0748233715599472
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and oxidative stress potential of nanosized and bulk zinc oxide particles in Drosophila melanogaster

Abstract: Zinc oxide nanoparticles (ZnONP) are manufactured on a large scale and can be found in a variety of consumer products, such as sunscreens, lotions, paints and food additives. Few studies have been carried out on its genotoxic potential and related mechanisms in whole organisms. In the present study, the in vivo genotoxic activity of ZnONP and its bulk form was assayed using the wing-spot test and comet assay in Drosophila melanogaster Additionally, a lipid peroxidation analysis using the thiobarbituric acid as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 79 publications
(125 reference statements)
1
13
0
Order By: Relevance
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) documented in vitro [7][8][9][10][11]28,80], but also in vivo [12,13], although other studies do not reach the same conclusion (e.g. [14]), and our results may shed new light in this area.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) documented in vitro [7][8][9][10][11]28,80], but also in vivo [12,13], although other studies do not reach the same conclusion (e.g. [14]), and our results may shed new light in this area.…”
Section: Discussionmentioning
confidence: 37%
“…There has been quite active research to determine the toxic mechanisms of these nanoparticles, and many papers imply the oxidative stress pathway, [6,7], leading to DNA damage and genotoxicity in vitro [8][9][10][11] but also in vivo [12,13], although this is still a controversial issue [14].…”
Section: Introductionmentioning
confidence: 99%
“…The ZnONPs have been reported to induce cytotoxicity, genotoxicity, and/or DNA damage in the root meristem cells of Allium cepa [47]; DNA damage in the epidermal cell line (A431) [48] and human neuroblastoma SHSY5Y cell line [49]; and somatic mutation and DNA damage in Drosophila melanogaster [50]. Also, Zn 2+ has been shown to cause significant DNA damage in Nicotiana tabacum in the root but not leaf cells, attributed to efficient H 2 O 2 scavenging by the enhanced antioxidative enzymes activity in leaf cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, several studies have shown that ZnO NPs or other types of NPs induce DNA damage in a variety of cell types. [50][51][52][53][54][55][56][57][58][59][60] In vivo exposure to ZnO NPs alters the structure of seminiferous tubules and spermatozoa morphologies…”
Section: Zno Nps Induce Nuclear Dna Leakage and Breakagementioning
confidence: 99%